2020
DOI: 10.3390/su122410438
|View full text |Cite
|
Sign up to set email alerts
|

Social Sustainability Strategy across the Supply Chain: A Conceptual Approach from the Organisational Perspective

Abstract: Much of the existing literature on the social aspects of sustainability in the supply chain has focused on dyadic buyer-supplier relationships. However, supply chains are much more extensive, featuring multi-tiered systems consisting of many interconnected sequential and parallel dyadic relationships; therefore, a more expansive and holistic approach to exploring the management and integration of social sustainability standards across the extended supply chain is desirable. This research attempts to help fill … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 86 publications
(248 reference statements)
0
11
0
Order By: Relevance
“…Social sustainability in organizations is a phenomenon broadly recognized as one of the most influential factors in organizations. However, in emerging economies, it is becoming popular in present days [ 96 ]. Successful organizations base their competitive advantage on their employees rather than technology and finance [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Social sustainability in organizations is a phenomenon broadly recognized as one of the most influential factors in organizations. However, in emerging economies, it is becoming popular in present days [ 96 ]. Successful organizations base their competitive advantage on their employees rather than technology and finance [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Eriksson and Svensson (2015) argued that social risks are more likely to be neglected by supply chain partners at varied levels of the manufacturing process. However, controlling the social dimensions of sustainability becomes more challenging across different levels of supply chain, mainly because focal organizations have less visibility and involvement in the operational activities of their suppliers (Najjar et al ., 2020). In terms of assessment and measurement of social risk, several studies reported that this risk could be managed and mitigated in the supply chain by accurately evaluating its impacts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…An important approach that major firms employ to monitor the socially responsible behavior of their suppliers is the Code of Conduct (Mani et al ., 2018). Najjar et al . (2020) argued that some factors that affect the efforts of supply chain sustainability, in addition to social risk, are stakeholder requirements for sustainability, location of transaction parties (buyers and suppliers), enforcement of sustainability regulation, cultural norms and trading volume.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to pressure from stakeholders who want socially responsible corporate operations, the concern for social sustainability has increased among supply chain managers and researchers alike (Najjar et al, 2020). Damert et al, (2020) created a SR-SCM framework to better comprehend the maintenance of social problems in SCs, a complete investigation demonstrating the relationship between stakeholder pressures and communication, compliance, and supplier development strategies.…”
Section: Social Sustainability: Extent Of Implementationmentioning
confidence: 99%